CHICKEN-POX PREVENTION BY THE SPECIFIC PREVENTIVE MEASURES IN BELARUS, KAZAKHSTAN, RUSSIA AND UKRAINE (STATEMENT OF EAST EUROPEAN VACCINE ADVISORY GROUP - EEVAG) - A.A. Baranov; D.N. Balashov; A.V. Gorelov; R.S. Idrisova; S.A. Kramarev; V.A. Matveev; L.S. Namazova; A.E. Platonov; V.V. Romanenko; A.G. Rumyantsev; V.K. Tatochenko; S.M. Kharit; et al. (Union of pediatricians of Russia, 2008)
In this announcement, a group of the leading world experts in the sphere of the vaccination are proud to present a strategic vision of the chicken-pox immuno prevention trends in the partner countries, as well as the basic recommendations for the vaccination in the partner countries.Key words: chicken-pox, vaccination, children.